A validation study for remote testing of cognitive function in multiple sclerosis. (April 2021) - Barcellos, Lisa F; Horton, Mary; Shao, Xiaorong; Bellesis, Kalliope H; Chinn, Terrence; Waubant, Emmanuelle; Bakshi, Nandini; Marcus, Jackie; Benedict, Ralph HB; Schaefer, Catherine
Objectives: Determine the validity and reliability of a remote, technician-guided cognitive assessment for multiple sclerosis (MS), incorporating the Symbol Digit Modalities Test (SDMT) and the California Verbal Learning Test, Second Edition (CVLT-II). Methods: In 100 patients, we compared conventional in-person testing to remote, web-assisted assessments, and in 36 patients, we assessed test–retest reliability using two equivalent, alternative forms. Results: In-person and remote-administered SDMT ( r  = 0.85) and CVLT-II ( r  = 0.71) results were very similar. Reliability was adequate and alternative forms of SDMT ( r  = 0.92) and CVLT-II ( r  = 0.81) produced similar results. Conclusions: Findings indicate remote assessment can provide valid, reliable measures of cognitive function in MS.